Perancangan Game Matematika Sebagai Media Pembelajaran Berbasis Android - Yulia Yulia (Innovation in Research of Informatics (INNOVATICS), 2019)
One technology that is developing very rapidly now is information technology and mobile communication (mobile). Mathematics is a science that is widely used in everyday life such as used in trade transactions, carpentry, and so forth. But unfortunately mathematics is considered a difficult subject to understand and is considered terrible by some students who do not like the subject. Like what happened at 004 Batu Aji State Elementary School in Batam. In addition, learning techniques are a bit rigid, because they only come from textbooks. Therefore an educational game was made by incorporating elements of mathematics learning in it to make it look interesting and increase students' interest in learning mathematics. The game to be built is an android-based math education game for grade 2 elementary school students. The variable indicators used are addition, subtraction, multiplication, division, and image installation. By incorporating elements of learning in it, the game can be used as an instructional system using mobile devices. The purpose of this study is to apply and develop mathematics learning media in the form of an android-based educational game in the hope that it can improve the ability to count quickly, add insight and memory to students. From the survey results obtained from elementary school student questionnaire 93.4% were satisfied with the Android-based mathematics education game application that was designed.